Adsorption of mesitylene via mesoporous adsorbents. (2nd December 2017) - Nien, Kai Chun; Chang, Feng Tang; Chang, Moo Been
ABSTRACT: Mesitylene (or 1, 3, 5-trimethylbenzene) is a volatile organic compound emitted from various industrial processes, e.g., spray coating. Its emissions have become a critical issue because mesitylene is toxic and cannot be removed using traditional adsorbents, e.g., zeolite (H-ZSM-5; the diameter of mesitylene molecules is greater than the pore size of H-ZSM-5). Hence, an adsorbent with a large pore size, MCM-41, is used in this study to investigate its adsorption capacity for mesitylene and compare with that of H-ZSM-5. Experimental results reveal that MCM-41 without Al2 O3 exhibits a good adsorption capacity (184 mg/g) for the gas stream containing 100 ppm of mesitylene at a relative humidity of 10%. The adsorption kinetics is well described by the Freundlich isotherm. Furthermore, experimental results reveal that MCM-41 is effective for the adsorption of low concentrations (10 ppm) of mesitylene. In addition, adsorption–desorption tests revealed that the sample MCM-41-AS is stable to sustain the adsorption capacity after 10 adsorption–desorption cycles. After 10 adsorption–desorption cycles, MCM-41-AS retains 92.4% of its initial adsorption capacity (170 vs. 184 mg/g). Finally, MCM-41 and H-ZSM-5 in series are effective for the simultaneous removal of mesitylene and toluene in the gas stream. Implications: This study aims to improve the performance of adsorbent for mesitylene, which is typically applied in the spray-coating industry. The zeolite MCM-41-AS is selected as a candidate for the investigation. Experimental results reveal that MCM-41-AS exhibits a good adsorption capacity for mesitylene and that it can be integrated with H-ZSM-5-25 for the simultaneous adsorption of mesitylene and toluene.